Organic bulk-heterojunction injected perovskite films for highly efficient solar cells. Issue 21 (14th May 2019) - Hu, Ke-Hao; Wang, Zhao-Kui; Meng, Li; Wang, Kai-Li; Zhang, Yue; Liao, Liang-Sheng
Abstract : The BHJ composed of PTB7 and ITIC was penetrated into the CH3 NH3 PbI3 layer via anti-solvent engineering. Abstract : Unsatisfactory light-harvesting over the wavelength of 500 nm is a critical factor limiting the further improvement in efficiency of halide lead based perovskite solar cells (PSCs). Past studies on a tandem strategy of integrating perovskite and bulk-heterojunction (BHJ) increased the fabrication complexity. Here, we developed a convenient strategy, injecting the organic BHJ of poly[[4, 8-bis[(2-ethylhexyl)oxy]benzo[1, 2- b :4, 5- b ′]dithiophene-2, 6-diyl][3-fluoro-2-[(2-ethylhexyl)-carbonyl]-thieno-[3, 4- b ]thiophenediyl]] (PTB7) and 3, 9-bis[2-(3-oxo-2-vinyl-2, 3-dihydroinden-1-ylidene)-malononitrile]-5, 5, 11, 11-tetrakis(4-hexylphenyl)-dithieno[2, 3- d :2′, 3′- d ′]- s -indaceno[1, 2- b :5, 6- b ′]dithiophene (ITIC) via anti-solvent engineering. Besides the function of enhanced light-harvesting in the range of 500–700 nm for the perovskite layer, the BHJ-treated CH3 NH3 PbI3 films exhibit superior crystalline quality with reduced defect and trap states. As a result, the resulting PSCs deliver a champion power conversion efficiency as high as 20%. The proposed method provides a facile route to integrate perovskite and organic BHJ conveniently by avoiding additional fabrication steps. And this method is suitable for large-scale and industrial production of high-performance PSCs.